Prevalence, patterns, and attitude regarding dietary supplement use in Saudi Arabia: Data from 2019. - Anwar M Alhashem; Rawan A Alghamdi; Rawan S Alamri; Wejdan S Alzhrani; Maha S Alrakaf; Njoud A Alzaid; Abeer S Alzaben (PLoS ONE, 2022)
Dietary supplements are products containing dietary elements including vitamins, minerals, amino acids, herbs, or botanicals. They can aid consumers with low dietary intake and quality, as well as those with high demands, by boosting nutritious value. A cross-sectional study was conducted among adults living in Saudi Arabia aged between 18-60 years old using online self-administered questionnaire. Information regarding sociodemographic characteristics, use and type of dietary supplements, and attitude toward and patterns of dietary supplement use was collected. The chi-square test, Pearson correlations, and the independent t-test were used. In total, 531 participants (115 men and 416 women) were included. Approximately half of the participants (51.8%, n = 275) used dietary supplements. Participants who were using dietary supplements were significantly younger (29.16 ± 9.32 years), more highly educated (85.5%, n = 235), and worked in the health sector (63.7%, n = 100). Herbal supplement use was associated with older age and female sex. Single mineral supplements were used more frequently by married, female, pregnant, or breastfeeding participants and those not working in the health sector. Fatty supplements were used more frequently by participants with a higher level of education. Regarding the attitude toward dietary supplement use, women, single participants, and health care workers showed a significant positive attitude. In-depth investigation into the amount of and reasons for dietary supplement use in the health sector is required. Additionally, educating pregnant and breastfeeding women on the importance of dietary supplements is necessary.